PENGARUH WORK LIFFE BALANCE TERHADAP EMPLOYEE PERFORMANCE DENGAN JOB STRESS DAN JOB COMMITMENT SEBAGAI VARIABEL MEDIASI: - - Farida I; Andreas Wahyu Gunawan P (FEB Universitas Sam Ratulangi Manado, 2023)
This study aims to analyze the effect of work life balance (WLB) which is thought to have an influence on employee performance (EP) with job stress (JS), job commitment (JC) as mediation. The data used in this study is primary data sourced from questionnaires distributed to respondents. The research sample is the Directorate General of Taxation employees who work in the KPP unit in the West Jakarta working area using the convenience sampling method so that 245 respondents are obtained as samples. Data analysis used to test the hypothesis used the PLS SEM (Partial Least Square Structural Equation Modeling (SEM)) analysis method. The results showed that work life balance has a positive effect on employee performance, job stress and job commitment can mediate the effect of work-life balance on employee performance